Etnomatemática: uma experiência na casa familiar rural de Breves/PA - OLIVEIRA, Odilson de Paiva (Universidade Federal do Pará, 2022)
We aim to analyze which contributions can be observed in the process of teaching mathematics from the development of activities from the perspective of Ethnomathematics at the Rural Family House Community School in the city of Breves/PA. We used D'Ambrosio's Ethnomathematics perspective, which presents it as a means of recognizing the influence of cultures in the way of dealing with everyday situations and problems. The participating subjects were: students from the EJA (Youth and Adult Education) fourth stage; the 3rd year high school class; the Forestry Technician at CFR. The reflections made lead us to infer that a work articulated between local cultural knowledge, linked to school mathematical knowledge and made possible by work from the perspective of Ethnomathematics provides a favorable environment for the formation of reflective students, capable of articulating the various knowledge (school and non-school students) in favor of their citizenship education.